The Legal Framework Of Apostasy in Egypt: A Manifestation Of Secular Reconstruction Of Sharia By A Modern State - Mohammed, Ahmed Sedky (AUC Knowledge Fountain, 2021)
The legal consequences of renouncing Islam or apostasy, which include depriving the apostate from some civil rights, and the non-recognition of the act itself by law in Egypt have been usually criticized as a blatant violation of the right to religious freedom. Such criticisms are based on the right’s definition according to international human rights law precisely the International Covenant on Civil and Political Rights. The dominant reasoning for this violation according to the majority of the related literature is the conservative interpretation of Sharia, the principal source of law, that has been adopted by Egyptian judiciary for more than fifty years. The advocates of this point of view argue that such violation could be resolved through adopting more lenient Sharia rulings concerning apostasy. Investigating the situation of apostasy from a broader legal perspective beyond the rhetoric of human rights demonstrates that resolving the complicated legal status of apostasy starts from realizing the legal framework of apostasy in Egypt as a single indication among others of legal pluralism. It is a problem that stems from the conflict between the rulings of both Sharia and IHRL, as law sources, regarding apostasy and their interpretation by the state. In light of its approach regarding constitutional Islamization, the Egyptian state through its legislature and judiciary has maintained the ambiguity of the legal situation of apostasy to balance between its constitutional obligation to apply Sharia and its international obligation to ensure the consistency of its laws with IHRL. Egyptian courts have undertaken this mission through reconstructing the application of some apostasy juristic and legal consequences under some secular legal regulations and the concept of public policy in contrast to the juristic position of apostasy according to Sharia.